The Effect of Info Graphics as Content Marketing On Consumer Attitudes - A Field Study for Smartphone Users in Lattakia Governorate - Xiaomi Official Website as A Model (Journal of Hama University, 2022)
This study aimed to determine the impact of infographics as content marketing on consumer attitudes, by studying the effect of infographics on the components of the three attitudes known in the literature (the cognitive component, the emotional component and the behavioral component), where a questionnaire was designed and distributed to a sample of mobile phone consumers in Lattakia, depending on the Google application for designing questionnaire forms. The researcher relied on the Xiaomi website as a model to measure this effect.The researcher concluded that there is an effect of the infographic on the components of the attitudes according to the following order (the cognitive component, the emotional component, the behavioral component), then the researcher presented, based on the results of the analysis of this model, a set of recommendations that increase the marketing ability of the Syrian companies that use the infographic as marketing content, especially the two companies, Immatel and Mabco.